Défense et illustration de la tragédie ‘à l’espagnole’ : La vida y muerte de Herodes de Tirso de Molina - Isabel Ibáñez (Etudes Epistémè)
Tirso de Molina’s La vida y muerte de Herodes, comedia was published in 1636 but composed at unknown date, generating some controversy over the matter. It presents a series of features associated to the tragic genre as defined by the requirements of Lope’s comedia, thus suggesting a pre 1617 date for its composition. The play was constructed around the figure of Herod with secondary characters embodying hubris as well as hamartia. The historical characters of the play are reconfigured to match the standards of Lope’s comedia. The play is characterized by the coexistence of contradictory theses: the question of tyranny and of the legitimacy of tyrannicide, the drama of connubial love that remains unresolved, and the Tridentine message of the Advent of Christ which upsets the hierarchy of the aforementioned issues. The play’s lack of resolution reveals its inconsistencies: focusing on the monstrous Herod does not allow the playwright to unravel a tragedy of hamartia and destiny in the way that plays written in 1620s Spain do. Indeed, comparing the play with tragedies by Calderón and Lozano, which are clearly rewritings of Tirso, testifies to these evolutions as Mariam came to replace Herod as the protagonist.